Organizational Culture on Job Satisfaction and Organizational Commitment on Organizational Citizenship Behavior in Employees. - Dian Anggriani Utina; Junaidin Junaidin (Economics and Digital Business Review, 2025)
This study investigates the influence of organizational culture and job satisfaction on organizational commitment and their subsequent impact on organizational citizenship behavior (OCB) among employees. Organizational culture plays a critical role in shaping workplace norms, attitudes, and values, thereby affecting employees’ satisfaction and their voluntary commitment beyond prescribed duties. Job satisfaction, as a key mediating variable, reflects employees' emotional responses to their roles and directly influences their commitment to organizational goals. Organizational commitment, in turn, fosters behaviors that go beyond formal job descriptions, collectively referred to as OCB. Using a quantitative research approach, this study collected data through surveys administered to employees across various industries. The findings indicate that a positive organizational culture significantly enhances job satisfaction, which strengthens employees' organizational commitment. Furthermore, a strong commitment positively correlates with the display of OCB, including altruism, conscientiousness, and civic virtue. These results underscore the importance of nurturing a supportive organizational culture and enhancing job satisfaction to cultivate a committed workforce capable of exceeding expectations. The implications of this study suggest that managers should prioritize cultural initiatives and satisfaction-driven policies to foster organizational commitment and encourage OCB, thereby improving overall organizational performance.